Helicobacter pylori: Factors Related to Therapeutic Resistance and Current Approaches (Global Journal of Human-Social Science, 2024)
bacterium poses a global health threat linked to chronic gastritis gastric ulcers and adenocarcinoma This literature review addresses H pylori challenges emphasizing therapeutic resistance and modern treatment strategies Methodology Original works published from 2019 to 2023 available in total and presenting experimental and clinical studies were included Results After the selection considering the inclusion and exclusion criteria 17 articles fulfilled the defined criteria The selected references were mainly from Brazil Vietnam Chile China Thailand the United States and Europe They highlight the growing antimicrobial resistance particularly against the first-line antibiotic clarithromycin Traditional triple therapies face growing compromise necessitating alternative approaches Vonoprazan VPZ -amoxicillin dual therapy stands out for acceptable eradication rates reduced resistance risk and enhanced safety Effective regimens include bismuth-free quadruple therapies and VPZ-based triple therapy proving efficacy even in high-resistance regions Clarithromycin resistance particularly in gastric remnants raises concerns about traditional triple therapy Resistance rates to metronidazole and clarithromycin underscore the importance of considering local resistance profiles when selecting treatments More research into the actions of drugs against H pylori is needed to help reduce future levels of antimicrobial resistance and minimize the significant impact on the gut microbiota
Keywords: antibacterial resistance; bacterial disease; chronic gastritis; dual therapy for H pylori